A field evaluation of coated urea with biodegradable materials and selected urease inhibitors - Junejo, Nasima; Yusop, Mohd Khanif; Dharejo, Khalil Ahmed; Abdu, Arifin; Abdul Hamid, Hazandy (Academic Journals, 2011)
Urease inhibitor and biodegradable polymer coatings are two most suitable startegies to increase urea fertilizer efficiency. Coating of urea with selected inhibitors can increase the crop production by slowing down the hydrolysis process of urea in the soil. For this purpose, a field experiment was conducted to evaluate the effects of newly coated urea with biodegradable materials, CuSO 4 and ZnSO 4. Guinea grass was used as a test crop. Six treatments (urea alone, palm stearin + Cu coated urea, agar + Cu coated urea, gelatin + Cu coated urea, Cu coated urea, and Zn + Cu coated urea) were applied to field plots as nitrogen sources at the recommended dose of urea (217 kg ha -1), with triple super phosphate (100 kg ha -1) and muriate of potash (217 kg ha -1). The soil and plant analyses were conducted by standard method for mineral N, soil pH and nutrient content of plant. The outcomes of the study showed 50% increase in dry matter yield and N uptake of grass and 20% reduction in ammonium accumulation on the soil surface in the coated urea plots. A concomitant decrease in soil pH to 4.2 or 4.3 was measured after 15 days of fertilizer application, which was due to the acidic effects of CuSO 4 and ZnSO 4. All coated urea treatments facilitated significantly for better pasture production and nutrient uptake.